Pembelajaran Bahasa Indonesia Menggunakan Microsoft Office Team 365 untuk SMA di Masa Pandemi - Aldi Dwi Saputra; Kundharu Saddhono (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2021)
Currently, the world is faced with a pandemic of Corona Virus Disease or COVID-19. All activities such as teaching and learning activities (KBM) at schools and universities must be carried out at home or carried out boldly with distance learning to prevent the spread of COVID-19. Distance learning is an option, even a necessity. One of the applications that can be used to support distance learning is Microsoft Office Team 365 as used in SMA Negeri 5 Surakarta. The purpose of this study was to see the use of Microsoft Office Team 365 learning media in bold learning in SMA Negeri 5 Surakarta during the Pandemic Period. The method in this research is case research. The subjects of this study were students of class XII SMA Negeri 5 Surakarta. In one class an average of 30 students. Microsoft Office Team 365 learning media can be used as online learning during a pandemic. The features available in Microsoft Office Team 365 can support bold learning during a pandemic. Distance learning using IT-based media can optimize the use of learning media for Microfost Office Team 365 so that class XII students of SMA Negeri 5 Surakarta still benefit from the distance learning process in the midst of the COVID-19 pandemic.